The intuitive case for naïve realism - Langsam, Harold (Philosophical explorations, 2017)
Naïve realism, the view that perceptual experiences are irreducible relations between subjects and external objects, has intuitive appeal, but this intuitive appeal is sometimes thought to be undermined by the possibility of certain kinds of hallucinations. In this paper, I present the intuitive case for naïve realism, and explain why this intuitive case is not undermined by the possibility of such hallucinations. Specifically, I present the intuitive case for naïve realism as arguing that the only way to make sense of the phenomenal character associated with perceptual experiences is by means of a naïve realist ontology. I then explain why this intuitive argument is not undermined by the possibility of hallucinatory experiences that possess the phenomenal character associated with perceptual experiences but, being hallucinations, do not have the ontological nature specified by naïve realism.